HORMONIOTHERAPY TREATMENT DOES NOT CHANGE THE STRENGTH HANDGRIP IN BREAST CANCER SURVIVORS WOMEN - Silva, Weder Alves da; Alves, Rafael Ribeiro; Vieira, Carlos Alexandre (International Journal of Movement Science and Rehabilitation, 2021)
Introduction: Hormone therapy is a type of efficient treatment against breast cancer. However, recent evidence has shown negative side effects on the general health status of women with this condition. In this sense, it is worth mentioning that muscle strength is an important component of physical fitness that is related to health. Objective: To compare the handgrip strength (HGS) of healthy individuals (HW) with breast cancer survivors (BCS) under hormonal treatment. Methodology: 10 women breast cancer survivors (BCS) who were undergoing hormone therapy and 10 healthy women (HW) were recruited. The handgrip strength test was performed in order to compare the values ​​between the groups. The independent T test was used to compare the averages of the parametric data between the groups. The level of significance was p≤0.05. Results: No differences were found between the BCS and HW groups in the right (25.5 ± 5.9 Kg and 27.0 ± 3.3 Kg, respectively (p= 0,09)) and left (24.2 ± 6.0 Kg and 26, 0 ± 4.3 Kg, respectively (p= 0,21)). Conclusion: We can consider that HGS was not influenced by hormonal treatment, showing similar values ​​between groups. Thus, health professionals can use this knowledge in order to enable strategies during hormonal therapy that require muscle strength such as the practice of physical exercise, in order to improve the prognosis of the disease.